High-energy collisions of organofullerene cations with helium. Ligand evaporation caused by encapsulation of the noble gas atom - Weiske, Thomas; Schwarz, Helmut; Hirsch, Andreas; Grösser, Thomas (Chemical Physics Letters, 1992)
High-energy collisions of C (H)CH (5 keV) with helium atoms demonstrate that, in the course of penetration of the fullerene cage, the organic ligands are stripped off from the fullerene surface resulting in the formation of C and He@C . This implies that energy is transferred to the CH and CC bond after the encounter complex is formed. © 1992.